WEB-BASED SYLLABLE READING LEARNING MEDIA (BASUKA) FOR BEGINNING READING FOR SLOW LEARNER STUDENTS AT ELEMENTARY SCHOOL LEVEL - Suci Noor Rahmawaty; Ravik Karsidi; Joko Yuwono (Journal of Disability, 2023)
Based on previous research and preliminary studies that have been carried out by researchers, to assist teachers in teaching beginning reading and for students in addition to beginning reading practice, researchers are interested in developing learning media combined with the beginning reading method, namely the syllabic method. This media is named "BASUKA Learning Media (read syllables)" which is a website-based application for beginning reading for slow learner students. This media is designed according to the initial reading stages and characteristics of slow learner children. This study aims to describe the feasibility of BASUKA (Read Syllable) media. The research was conducted in 2 Elementary Schools Providing Inclusion Education, namely SDN Rambutan 01 and SDN Susukan 01. This research uses a research and development (R&D) approach with the Borg and Gall procedure. The subjects at the testing stage in small-scale trials were 8 Slow Learner students and a large-scale trial sample of 20 Slow Learner students. The results of the study were concluded as follows: 1) Syllabic Reading learning media (BASUKA) is needed in learning to read the beginning of Slow Learner students in inclusive education provider schools 2) Development procedures include: a) Making application designs; b) Compile a guidebook; c) BASUKA Media Development. 3) Product feasibility results on expert validation, small-scale trials, and large-scale trials have been declared feasible. 4) Effectiveness test results.